Sniper's honor : a Bob Lee Swagger novel - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel, 2014)
"Bob Lee Swagger is in love--with a woman who died 70 years ago. Ludmilla "Mili" Petrova was a great Russian sniper in World War II until she disappeared on a mission and was virtually erased from history. When Kathy Reilly of the Washington Post encounters a brief mention of Petrova in an old Russian propaganda magazine, she begins building a story around the legendary female sniper, who was once dubbed Die Weisse Hexe--The White Witch--and lauded by enemies and comrades alike. Mili's luxurious blonde hair and statuesque figure belied her fierce resolve to avenge the deaths of her husband and family by joining Stalin's Army and using her sharpshooting expertise to defeat Hitler's organization--ideally from the top down. There is very little on record for Reilly to mine for her profile, which only makes her want to dig deeper, enlisting her friend and former marine sniper Bob Lee Swagger to parse out the scarce details of Mili's astonishing military service. The more Swagger learns about the circumstances of Mili's last mission, the more he reveres the beautiful Russian heroine and longs to have known a fellow sniper with such courage and skill. And the more he believes her disappearance was no accident, and that Mili Petrova, while an essential player in Stalin's master plan, was merely a pawn in some larger conspiracy. But why would the Russian government go to such great lengths to erase one of their own decorated, legendary soldiers from history? And why, when Swagger joins Kathy Reilly on a research trip to the Carpathian Mountains, is someone trying to kill them for what they might find?"--